MAKNA TRADISI KHATAM AL-QUR'AN PADA UPACARA PERNIKAHAN DI DESA RAHUNING 1, ASAHAN - Destia Luvita Sari (Jurnal Budaya Nusantara, 2022)
This study seeks to reveal the tradition and process of implementing Khatam Al-Qur'an at a wedding ceremony in Rahuning I village, Asahan Regency. Khatam Al-Qur'an is one of the common rituals performed by people who want to get married, especially in Rahuning I Village, Asahan Regency. Khatam Al-Qur'an literally means that you have finished learning to read the Qur'an. However, at the wedding ceremony in Rahuning I village, khatam Al-Qur'an is not only interpreted as a form of gratitude for the ability to read the Qur'an, but also as a sign of gratitude to the teacher who teaches reading the Qur'an, and as a reminder that the Qur'an must continue to be used as a guide in the household's ark later, and with the Qur'an the household will be blessed with many blessings from Allah SWT. This study uses a descriptive qualitative research method with a phenomological approach. By extracting data through observation, and in-depth interviews with the Koran teacher (the person who finishes the process), the bride (the person who finishes it), and people who are involved in the tradition. The implementation of this tradition begins with making a hall (bale), opening by the Koran teacher, reading the surah of the Qur'an starting from Surah Ad-Dhuha to Surah Annas which is read in rotation by 5 or more people, praying for the completion of the Koran, handing over the hall (bale) to the Koran teacher, and finally sungkem to the Koran teacher and the two parents.